Study on chloride ion resistance durability and mechanism of nano modified concrete sea sand mortar - Fan, Wei; Jin, Yingjie; Wu, Shengping (Frontiers in Materials, 2025)
This study incorporated nanomaterials to modify traditional sea sand mortar to enhance the durability of marine infrastructure. It explored the effects of nano-silica (NS), nano-metakaolin (NMK), and nano-alumina (NA)) on the chloride binding capacity and microstructure of the sea sand mortar through potentiometric titration, X-ray diffraction (XRD), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). The results indicated a significant enhancement in the chloride binding capacity of the nanomaterial-modified sea sand mortar. Both NS and NMK reduced Friedel’s salt (FS) content in sea sand mortar while enhancing chloride binding capacity via increased physical adsorption. NA increased the FS content in sea sand mortar, thereby enhancing its chemical bonding capacity for chloride ions. Among these three nanomaterials, NMK demonstrated the best improvement in the pore structure of sea sand mortar, followed by NS. The research results provide an innovative material solution for marine engineering structures.